POTRET KEARIFAN LOKAL, PERUBAHAN IKLIM DAN PENGGARUHNYA TERHADAP PRODUKTIVITAS PADI SAWAH DI SALATIGA - Athanasius Aditya Wisnu Graha; - Yuliawati (Agric, 2015)
The research about portrait of local wisdom, climate change and the factors that affect the productivity of paddy was held on December 20, 2013 until March 21, 2014 in Kauman Kidul village, Sidorejo sub-district, Salatiga. The purposes of this study were 1) describing the portrait of local wisdom of farmers in Salatiga, 2) examining the effect of the seeds, fertilizers, pesticides, labors from the family members and outside family members, farming experience, local wisdom, climate change toward paddy’s productivity,and 3) examining the differences of paddy’s productivity and farmer’s income in 2009 and 2012. Samples were taken purposively, consist of 30 paddy’s farmer. Primary data were collected by survey method through interviewing by using structured questionnairesand secondary data collection is done by quoting monograph data and other documents related to the study. Data analysis using Cobb - Douglass production function with linear regression models were transformed into natural logarithm. The result of this study show that 1) there is local wisdom before planting and harvesting 2) partially, the fertilizers, pesticides, labors from outside the family members, local wisdom affect the paddy’s productivity, nevertheless the seeds, labors from family members, farming experience and climate change do not affect paddy’s productivity. Also 3) no prominent differences was found from the paddy’s productivity before and after the climate change, however there is prominent differences between the income before and during the climate change.